SURGICAL MANAGEMENT OF POST-BURN SCAR EXTENSION CONTRACTURES OF THE TOES - E.K. IBRAGIMOV; A.A. DAVLATOV; M.KH. MALIKOV; M.R. KHAYDAROV; N.KH. KHAMIDOV; N.A. MAKHMADKULOVA (Avicenna Tajik State Medical University, 2022)
Objective: To study surgical management of post-burn scar extension contractures of the toes. Methods: The treatment outcomes of 72 children with post-burn scar extension contractures of the toes between the ages of 3-15 were analysed. There were 38 boys (52.8%), girls - 34 (47.2%). In 14 (19.4%) children, both feet were affected, with a total of 86 feet with extension contracture. In most cases (n=53, 73.6%) of children (62 feet), retracting scars extending proximally also caused extension contracture of the ankle joint. Results: In all cases, a modified Z-plasty (butterfly flap) technique, according to Hirshowitz, was used to correct scar contracture of the anterior ankle. In 89.5% of patients (77 feet) after reconstruction using a local flap, soft tissue defects (range, 6-30 cm2) remained. The defects were covered with full-thickness autologous skin grafts. In this case, in 32.6% (28 feet), the exposed tendons and cutaneous nerves were preliminarily covered by the surrounding subcutaneous tissue and fascia used as a blood-supplying source. Local flap surgery helped reconstruct mild scar contracture in 16 (18.6%) feet. In 21 (24.4%) cases, tendon-articular structures were reconstructed. Complications in the early postoperative period were observed in 7 out of 86 operated feet, which amounted to 8.1%. In all cases, complications included marginal necrosis of local flaps and transplanted full-thickness skin grafts observed in 4 feet (4.6%) and 3 (3.5%) feet, respectively. In all cases, engrafting of a full-thickness skin graft was noted; and there was no complete recurrence of contracture. Due to the somatic growth of children in 8 cases (9.3%) in the late postoperative period (after 6-10 years), repeated corrective surgical procedures were required. Conclusion: In children, burn contractures of the toes require surgical intervention on the skin and soft tissue. Unfortunately, the pathological process is almost always accompanied by a lack of skin and soft tissue, requiring skin grafts. In the long term, there is a need for repeated corrective surgical interventions.